PERCEPTIONS OF COMMUNICATION SCIENCE STUDENTS CLASS OF 2018 TOWARDS THE TIK TOK APPLICATION AS A MEDIUM FOR SOMEONE'S POPULARITY - BR Ginting, Asih Permata Bunda; Alfikri, Muhammad (Universitas Dharmawangsa, 2022)
Increasingly sophisticated technology never satisfies desires and even encougares human curiosly. One of the influences of technology that cannot be separated from life is social media. Â Moreover, social media can help someone become famous. Â So this becomes a special attraction for pandemic, the TiokTok application was paresent in the midst of the community to accompany when rsearcherswant to find out how Â students perceive the application.